WIP, YAP/TAZ and Actin Connections Orchestrate Development and Transformation in the Central Nervous System - Antón, Inés M.; Wandosell, Francisco (Frontiers in Cell and Developmental Biology, 2021)
YAP (Yes-associated protein) and TAZ (transcriptional coactivator with PDZ-binding motif) are transcription co-regulators that make up the terminal components of the Hippo signaling pathway, which plays a role in organ size control and derived tissue homeostasis through regulation of the proliferation, differentiation and apoptosis of a wide variety of differentiated and stem cells. Hippo/YAP signaling contributes to normal development of the nervous system, as it participates in self-renewal of neural stem cells, proliferation of neural progenitor cells and differentiation, activation and myelination of glial cells. Not surprisingly, alterations in this pathway underlie the development of severe neurological diseases. In glioblastomas, YAP and TAZ levels directly correlate with the amount of the actin-binding molecule WIP (WASP interacting protein), which regulates stemness and invasiveness. In neurons, WIP modulates cytoskeleton dynamics through actin polymerization/depolymerization and acts as a negative regulator of neuritogenesis, dendrite branching and dendritic spine formation. Our working hypothesis is that WIP regulates the YAP/TAZ pools using a Hippo-independent pathway. Thus, in this review we will present some of the data that links WIP, YAP and TAZ, with a focus on their function in cells from the central and peripheral nervous systems. It is hoped that a better understanding of the mechanisms involved in brain and nervous development and the pathologies that arise due to their alteration will reveal novel therapeutic targets for neurologic diseases.